Profesionalisme Perwira Hukum Dalam Membangun Visi-Misi Hukum Militer Dalam Rangka Menghadapi Tantangan Tugas TNI Di Masa Depan - Arief Fahmi Lubis (Jurnal Media Administrasi, 2019)
The role of Legal Officers has a strategic position both in formulating regulations and also providing legal opinion advice so that TNI leadership is correct in making decisions. Legal officers also carry out different roles in implementing the main tasks, namely ensuring that all duties carried out by Soldiers are carried out correctly in accordance with applicable legal regulations, therefore the professionalism of legal officers is manifested in several fields. The purpose of this research is to emphasize that the position and role of Legal Officers is very important because bureaucratic reform must be carried out in accordance with statutory provisions. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description at the time of the research. The results of this research show that the role of Legal Officers has a strategic position both in formulating regulations and also providing legal opinion advice so that TNI leadership is appropriate in making decisions.